2015
DOI: 10.11646/zootaxa.3994.4.1
|View full text |Cite
|
Sign up to set email alerts
|

New taxonomic and distributional information on hermit crabs (Crustacea: Anomura: Paguroidea) from the Gulf of Mexico, Caribbean Sea, and Atlantic coast of South America

Abstract: A collection of Paguroidea recently obtained during deep-water expeditions along the coast of Brazil, forms the basis of this report. Of the 14 species reported from Brazil, 11 represent range extensions to the south, and one, Michelopagurus atlanticus (Bouvier, 1922), is a first record for the western Atlantic. The specimens were compared with types and western Atlantic materials deposited in various major museums. A diagnosis and illustrations are presented for each of seven species found to be poorly or ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…New references for different geographic sectors have been given by Ingle (1993), García Raso (1982aRaso ( , 1984bRaso ( , 1985c, and the ECO-MARG (IEO) 2005 and 2006 Expeditions, among others (see Appendix 1). Seven species of pagurids have been added since Zariquiey Álvarez (1968): Anapagurus alboranensis, described from the Alboran Sea by García-Gómez (1994) and later recorded in the Gulf of Cádiz (Manjón-Cabeza and García Raso 1998) and along the Spanish Mediterranean coasts (Macpherson and Raventos 2004); Anapagurus pusillus, captured in Atlantic waters in southern and western Portugal (García-Gómez 1994, Sampaio et al 2016 and in northern Spain (Cantabria, ECOMARG IEO, Serrano et al 2006); Catapaguroides iris, captured in the Gulf of Cádiz (one specimen from INDEMARES-Chica 0211, García Raso unpublished data), previously known in Azores and the north of Morocco (Ingle 1993; Pagurus pseudosculptimanus, described by García Muñoz et al (2014) and recorded in the Alboran Sea; the African Pagurus mbizi, which is penetrating into the Mediterranean through the Alboran Sea (García Raso et al 2014b); Pagurus pubescentulus, recorded in Cantabria (IEO ECOMARG, Serrano et al 2006); and Michelopagurus atlanticus, a deep-sea (790-1575 m according to Lemaitre and Tavares 2015) amphi-Atlantic species recently found off Aveiro, Costa de Prata (western Portugal) at a much shallower depth (41 m) by Sampaio et al (2016), which is noteworthy. Also, the occurrence of Anapagurus smythi Ingle, 1993 in the Cantabrian Sea (IEO ECOMARG http://www.…”
Section: Taxonomic Groupsmentioning
confidence: 94%
“…New references for different geographic sectors have been given by Ingle (1993), García Raso (1982aRaso ( , 1984bRaso ( , 1985c, and the ECO-MARG (IEO) 2005 and 2006 Expeditions, among others (see Appendix 1). Seven species of pagurids have been added since Zariquiey Álvarez (1968): Anapagurus alboranensis, described from the Alboran Sea by García-Gómez (1994) and later recorded in the Gulf of Cádiz (Manjón-Cabeza and García Raso 1998) and along the Spanish Mediterranean coasts (Macpherson and Raventos 2004); Anapagurus pusillus, captured in Atlantic waters in southern and western Portugal (García-Gómez 1994, Sampaio et al 2016 and in northern Spain (Cantabria, ECOMARG IEO, Serrano et al 2006); Catapaguroides iris, captured in the Gulf of Cádiz (one specimen from INDEMARES-Chica 0211, García Raso unpublished data), previously known in Azores and the north of Morocco (Ingle 1993; Pagurus pseudosculptimanus, described by García Muñoz et al (2014) and recorded in the Alboran Sea; the African Pagurus mbizi, which is penetrating into the Mediterranean through the Alboran Sea (García Raso et al 2014b); Pagurus pubescentulus, recorded in Cantabria (IEO ECOMARG, Serrano et al 2006); and Michelopagurus atlanticus, a deep-sea (790-1575 m according to Lemaitre and Tavares 2015) amphi-Atlantic species recently found off Aveiro, Costa de Prata (western Portugal) at a much shallower depth (41 m) by Sampaio et al (2016), which is noteworthy. Also, the occurrence of Anapagurus smythi Ingle, 1993 in the Cantabrian Sea (IEO ECOMARG http://www.…”
Section: Taxonomic Groupsmentioning
confidence: 94%
“…300 m. This has already led to various new species discoveries (Van Tassell et al 2012;Baldwin and Johnson 2014;Baldwin and Robertson 2013Harasewych 2014;Van Soest et al 2014;Harasewych and Tëmkin 2015;Baldwin et al 2016;Tornabene et al 2016a, b), new distribution records (Pawson and Pawson 2013;Fransen 2014;Lemaitre and Tavares 2015), as well as new depth records for some species (Van der Meij et al 2015;Tornabene et al 2016c;Hoeksema et al 2017a).…”
Section: Caribbean Seamentioning
confidence: 98%
“…Numerous checklists, observational accounts, ecological studies, and taxonomic keys do not address details of coloration or morphology among the specimens they designate as P. tortugae s.l. (Schmitt 1935;Wass 1955;Provenzano 1961;Soto 1980;Holmquist 1989;Martinez-Iglesias & Gomez 1989;Mantelatto & Sousa 2000;Majon-Cabezas et al 2002;Mantelatto & Garcia 2002a, 2002b, 2002cRaz-Guzman et al 2004;Rahayu 2005;Tagliafico et al 2005;Barros-Alves et al 2015;Lemaitre & Tavares 2015;Poupin 2018). Thus, our herein reported synonymies applicable to P. karenae n. sp.…”
Section: Family Diogenidae Ortmann 1892mentioning
confidence: 99%
“…Phylogenetic analysis of available genetic data in some cases suggested the inclusion of Areopaguristes tudgei (Bracken-Grissom et al 2013Craig & Felder 2021) and A. hummi (Wass, 1955) (Bracken-Grissom et al 2013), although morphological arguments for these assignments were not conclusive . With these additions, the P. tortugae complex now spans a broad geographic distribution throughout the western Atlantic (Felder et al 2009;Lemaitre & Tavares 2015), with constituent species found across multiple ecoregions (Spalding et al 2007) from the Carolinean province on the eastern coast of North America, southwards beyond Rio de Janerio, Brazil (Table 1). Two additional previously unnamed western Atlantic species associated with the complex are herein formally described based upon morphology, coloration, and insights from DNA-based phylogenetic analyses.…”
Section: Introductionmentioning
confidence: 99%